Production of Rabbit Anti-Rabies Immunoglobulin Using Cultural Antigen - S. V. Generalov; E. G. Abramova; Zh. V. Matveeva; I. M. Zhulidov; O. A. Lobovikova; L. V. Savitskaya; L. N. Minaeva; M. V. Galkina; T. A. Mikheeva; A. V. Komissarov; M. N. Kireev; A. K. Nikiforov (Проблемы особо опасных инфекций, 2012)
Justified is the possibility of application of fixed rabies virus Moscow 3253, reproduced on the cell culture Vero, as an antigen for heterologous anti-rabies immunoglobulin production. Application of the adjuvant - aluminium hydrate - is determined to be effective. Herein, by the day 73 post immunization, specific antibodies titer is ≥ 1:500 (wherein specific activity has been identified by means of neutralization test, carried out on white mice, and dot-blot immunoassay). The level of specific activity in experimental samples of anti-rabies immunoglobulin, isolated from rabbit immune serum, corresponds to 332 and 347 ME/ml. Physicochemical and biological properties of anti-rabies immunoglobulin, produced with the help of cultural antigen, fully comply with regulatory requirements specified for commercial preparation of heterologous anti-rabies immunoglobulin.